Role of effective communication to ensure community participation in NGOs' projects: A comparative study of a Malaysian and a Pakistani NGO / Mumtaz Ali - Ali, Mumtaz (2014)

(untitled)
In today‟s world social issues can be seen in the form of conflict, discrimination, poverty, low quality human resources and unequal distribution of resources, thereby leaving communities marginalized and deprived. Community development is one way of building the capacity of people and involving them in finding the solutions to such problems. Community development also has much potential to build community cohesion by facilitating and supporting a community‟s commitment and strengthening connections among individuals, organizations and local groups. Community participation in development projects is important and vital for the success of any initiative. To have a successful outcome, effective participation is important. Information and knowledge sharing among people can be attained through effective communication. Previously, the management of non-governmental organizations was seen as esoteric and irrelevant but now-a-days there is much greater interest to do this management efficiently and effectively. There are various NGOs in Malaysia and Pakistan which can be sub-categorized as welfare and charity, health care and medical, youth and sports etc. Effective communication within such NGOs is essential to run development projects successfully. The five-rung ladder of participation by Wilcox (1994) relates to the stance that an organization may take for promoting participation- information sharing, consultation, deciding together, acting together and supporting independent community interests. This study examines this flow of communication in one Malaysian and one Pakistani NGO (FRHAM from Malaysia and HANDS from Pakistan). The researcher has described and analyzed how bottom up and the top down approaches are put into practice in these two NGOs. These NGOs need to determine how important the level of communication adaptation works in their respective contexts. The data collected from these NGOs is analyzed based on the theory of Wilcox (1994) and the theory by Weick (1969). Questionnaires were used and interviews were conducted to obtain the data from 10 officials of each NGO (n= 10+10 = 20) and 200 members of the community (n= 100 + 100 = 200) of the respective NGOs. Interviews were conducted with five key informants from each country (n=5+5=10). Statistical analysis was conducted using the quantitative data and qualitative analysis was made based on the interviews with key informants. The findings show a lack of a communication protocol with communities. This research added value to the body of existing knowledge by extending clarity on the subject for the purpose of the adaption and standardization of the communication system of NGOs. The data showed that the communication system of NGOs is an important factor to ensure community participation. A proper community participation mechanism needs to be implemented. The study results in a model named „Communication, Participation and Cooperation (CPC)‟ which is a way forward towards community empowerment.